Evaluation of the Efficacy and Safety of Chinese Herbal Injection Combined With Trimetazidine for Viral Myocarditis: A Network Meta-Analysis - Kerui Wu; Dingwei Deng; Binghui Yu; Ziyun Han; Lanlin Huang; Yaxing He; Xia Yan; Dawei Wang (Frontiers Media S.A., 2021)
Background: Viral myocarditis (VMC) is a common emergency of cardiovascular disease. Current treatment for VMC includes the prohibition of exercise plus supportive and symptomatic treatment, given the lack of specific antiviral therapeutic options and insufficient evidence for the use of novel immunosuppressive therapies. Trimetazidine, a drug used to improve myocardial energy metabolism, is frequently used for the treatment of viral myocarditis. In China, Chinese herbal injections (CHIs) are often used in combination with trimetazidine. Therefore, we evaluate the efficacy and safety of CHI combined with trimetazidine in the treatment of VMC through the method of network meta-analysis.Methods: We searched PubMed, the Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Scientific Journals Full-text Database (VIP), and China Biology Medicine Database (CBM) databases from inception to September 1, 2020, to identify eligible randomized controlled trials. The Cochrane risk of bias tool was used to assess the risk of bias among selected studies and the Stata 16.0 software was used to perform the network meta-analysis.Results: A total of 29 studies were included, representing data from 2,687 patients. The effectiveness rate, level of myocardial injury marker, and the adverse reaction rate were evaluated. Compared with conventional treatment or conventional treatment combined with trimetazidine, CHIs combined with trimetazidine appeared to have a better therapeutic effect, with higher effectiveness rate and better reduction of the levels of creatine kinase, creatine kinase-MB, and lactate dehydrogenase. Based on surface under the cumulative ranking, Shenmai injection combined with trimetazidine appeared to be superior in terms of effective rate, while Astragalus injection or Salviae miltiorrhizae and ligustrazine hydrochloride injection combined with trimetazidine appeared most effective in reducing myocardial injury markers. There was no significant difference in safety between the interventions. However, a lack of safety monitoring in some selected studies meant that the safety of some interventions could not be fully evaluated.Conclusion: CHIs combined with trimetazidine may have therapeutic value in the treatment of viral myocarditis, and Shenmai injection, Astragalus injection, and Salviae miltiorrhizae and ligustrazine hydrochloride injection may represent the most effective CHIs. Further clinical investigation is required to confirm these results.